Indications and outcomes for repeat cytoreductive surgery and heated intra-peritoneal chemotherapy in peritoneal surface malignancy. (September 2021) - Sutton, P.A.; O'Dwyer, S.T.; Barriuso, J.; Aziz, O.; Selvasekar, C.R.; Renehan, A.G.; Wilson, M.S.
Abstract: Introduction: Cytoreductive surgery (CRS) and heated intraperitoneal chemotherapy (HIPEC) is offered in specialist centres as a treatment for peritoneal surface tumours. Despite its demonstrated efficacy, intra-abdominal recurrence occurs in 31–57% of patients. The aim of this study is to review the early and long-term outcomes in patients who undergo repeat CRS/HIPEC. Materials and methods: A retrospective review of a prospectively maintained database of patients who had undergone repeat CRS/HIPEC for appendiceal neoplasms and colorectal peritoneal metastases (CRPM) from 2003 to 2019 was performed at a single specialist centre. Data pertaining to both short term outcomes and survival were evaluated. Results: Of 1259 patients who had undergone CRS/HIPEC, 84(6.7%) underwent repeat surgery: 45(53.6%) had pseudomyxoma peritonei (PMP) secondary to low grade appendiceal mucinous neoplasms (LAMN), 21(25.0%) had appendix carcinoma and 18(21.4%) had CRPM. Demographics, intra-operative findings and short-term outcomes were comparable across tumour types and between procedures. Median (95% CI) interval between procedures was 22.7(18.9–26.6) months and was comparable between tumour types. Median (95%CI) overall survival was not reached for the cohort overall or for those with PMP, but was 61.0(32.6–89.4) months for those with appendix cancer and 76.9(47.4–106.4) months for CRPM (p=<0.001). Survival was favourable in the PMP group (HR [95%CI] 0.044 [0.008–0.262]; p = 0.000) and unfavourable in the CC2-3 at index CRS procedure group (HR [95%CI] 25.612 [2.703–242.703]; p = 0.005). Conclusion: Our findings demonstrate that repeat cytoredutive surgery with HIPEC can result in favourable survival, especially for patients with PMP when complete cytoreduction is achieved at index operation. We recommend that detailed patient assessment is performed through an expert multidisciplinary team meeting (MDT). Highlights: Repeat CRS/HIPEC is safe, with comparable morbidity to the index procedure. Repeat CRS/HIPEC results in favourable survival, especially in PMP with CC0. Median survival was 61.0 and 76.9 months for appendix carcinoma and CRPM respectively. Median overall survival was not reached for the cohort overall, or for those with PMP. Detailed patient assessment should be performed by an expert multidisciplinary team.